Peran Taman Pendidikan Al - Quran (TPA) dalam Meningkatkan Kemampuan Membaca Al - Quran dan Membangun Akhlakul Karimah bagi Peserta Didik di TPA Syuhada, Dusun Sumber Jaya, Desa Mukti Makmur Kecamatan Simpang Kiri, Kabupaten Subulussalam - Septia Sakinah Rizki Utama; Yuli Ekawati; Pratista Andanitya Siregar; Abdi Abdi; Fahrurrozi Hutasoit (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
Islam views value education as the core of education itself. The value in question means morals, namely values derived from the origin of the teachings of Islam which are sourced from the Quran and Hadith. The purpose of value education which is the goal of moral education is to carry out God's commands, not just to receive wealth, power, enjoyment, or global happiness. Therefore, we can understand that value education in the teachings of Islamic beliefs has a crucial role in realizing a complete human being or human being. TPA is an area where students will become future leaders. Children today are potential leaders. At TPA, students are brave, commendable, and honest, study hard, good at reading the Qur'an, and have a high monotheistic spirit. The purpose of this study was to determine the role of the Qur'an education park in improving the ability to read the Qur'an to build morals at the Syuhada TPA Syuhada Dusun Sumber Jaya, Mukti Makmur Village. This research was conducted using a qualitative descriptive approach, the researcher became the instrument. The research uses a qualitative approach because the problems discussed are not related to numbers, but describe, describe and describe the role of the Al-Qur'an educational park in improving the ability to read the Qur'an and build the morals of students at TPA Syuhada di Dusun sumber Jaya, Rw 4, Kampung Mukti Makmur, Kecamatan Simpang Kiri, Kota Subulussalam, Tahun 2014. From the results of this study that the role of the Al Quran Education Park in improving the ability to read the Koran and building akhlakul Karimah for students at the TPA Syuhada Dusun Sumber Jaya, it is very relatively good this can be seen from what will happen to the learning and assessment carried out by the students who show that most of the students have been able to read the Qur'an properly and correctly according to what is needed by the TPA. The TPA also builds akhlakul karimah such as, several times the spectacle related to the good morals of the prophets, friends, or the work of friends out there who are then able to increase faith as well. After that, reading books that are able to support this are provided. In addition, to add knowledge about worship at the Koran Koran so that they can carry out worship according to the guidance that has been taught, the expectations conveyed are able to be imprinted exclusively on the students at the recitation, as a result of which the students are able to live life on a daily basis appropriate day using the guidance that has been taught.